2005
DOI: 10.1590/s0100-06832005000500002
|View full text |Cite
|
Sign up to set email alerts
|

Modelagem numérica para o processo da evaporação da água do solo

Abstract: RESUMOForam realizados vários ensaios laboratoriais para avaliar o desempenho de um modelo numérico em simular o processo unidimensional da evaporação da água do solo. Este modelo foi desenvolvido a partir da linearização da equação de Richards no espaço e do uso da técnica iterativa de Newton-Raphson, para resolver essa equação não-linear no tempo, e leva em conta o fluxo de vapor dentro do perfil de solo e a taxa de evaporação na sua superfície. Os resultados mostraram que o modelo foi capaz de simular satis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 5 publications
0
1
0
2
Order By: Relevance
“…In the following day, it rained in the morning and in the afternoon, and on 12/03/08 initiated humid and having high evaporation. After 7 days without rain, it was observed that treatment with 10 t ha -1 had lower evaporation rates than the other treatments, a fact that confirms PREVEDELLO & LOYOLA (2005), simulating the evaporation process, found that sand placed on the soil surface, behaves as an insulating layer ("mulching"), providing strong resistance to the flow of water on the soil surface. Also GONÇALVES et al (2005) evaluated the water consumption of lettuce crop with the soil covered with polyethylene film, and observed water consumption about 34% lower compared to the lettuce which treatment did not have the soil covered with plastic.…”
Section: Daily Values Of Evaporationmentioning
confidence: 55%
“…In the following day, it rained in the morning and in the afternoon, and on 12/03/08 initiated humid and having high evaporation. After 7 days without rain, it was observed that treatment with 10 t ha -1 had lower evaporation rates than the other treatments, a fact that confirms PREVEDELLO & LOYOLA (2005), simulating the evaporation process, found that sand placed on the soil surface, behaves as an insulating layer ("mulching"), providing strong resistance to the flow of water on the soil surface. Also GONÇALVES et al (2005) evaluated the water consumption of lettuce crop with the soil covered with polyethylene film, and observed water consumption about 34% lower compared to the lettuce which treatment did not have the soil covered with plastic.…”
Section: Daily Values Of Evaporationmentioning
confidence: 55%
“…A tabela 2 mostra a quantidade de água usada para cada nível de saturação. [10], e, portanto, com uma tendência a criar macroporos com uma variabilidade e frequência maiores do que uma de abertura menor. Ademais devido à natureza do sensor devemos optar entre duas opções ao realizar sua calibração: Homogeneizar a amostra entre as trocas de sensores visando evitar que os sucessivos furos provocados pelo sensor criem alterações na estrutura da amostra, porém com a consequência de alterar sua estrutura e, portanto, os valores de leitura.…”
Section: Resultsunclassified
“…Muitos autores têm procurado estabelecer modelos matemáticos para estimar as propriedades hidráulicas dos meios porosos, a partir de outros modelos mais facilmente mensuráveis (Mualem, 1976;Genuchten, 1980, Prevedello & Loyola, 2005.…”
unclassified